Phytophthora cinnamomi and oak decline in southern Europe. Environmental constraints including climate change - Brasier, C M (Ann. For. Sci., 1996)
One of the most destructive of all tree root pathogens, the oomycete fungus Phytophthora cinnamomi, is associated with mortality and decline of Quercus suber and Q ilex in the Mediterranean region. The symptoms and distribution of this decline are described. P cinnamomi is a primary pathogen on a very wide range of trees and woody ornamentals worldwide, but is probably a native of the Papua New Guinea region. It is soil borne and requires warm, wet soils to infect roots. Since 1900 it has caused major epidemics on native chestnuts in the United States and Europe, and now threatens the stability of entire forest and heath communities ecosystems in some parts of Australia. Together with drought, it may be a major predisposing factor in the Iberian oak decline. Its possible role in this decline including its interaction with drought is discussed, and a generalised working hypothesis of decline is presented. The potential influence of climate warming on the activity of P cinnamomi is also considered. A model based on the CLIMEX program suggests that warming would significantly enhance the activity of the pathogen at its existing disease locations (such as the western Mediterranean and coastal northwest Europe), but that it would not greatly extend its activity into areas with cold winters such as central and eastern Europe
Keywords: climate change; Drought; Oak decline; phytophthora cinnamomi; root pathogen